(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is backbone about India’s economy because it supports over half about country’s population. continued success about agriculture is now seriously threatened through changes in weather, climate, & other environmental factors. choice help device for Crop Yield and nutrition Prediction (CYP), which remembers helping choices for which yields towards plant & what towards do during development time about yields, is where AI (ML) assumes an imperative part. CYP traits are primary focus about current study, which is organized around a systematic review. Likewise, various procedures have been made towards break down agrarian creation forecast using computer based intelligence strategies. main disadvantages about neural network are a lower accuracy in crop yield prediction & a lower relative error. Like this, managed learning calculations neglected towards perceive nonlinear connection among info & result factors, which introduced a test during choice, reviewing, or arranging about natural products. Numerous studies were encouraged towards establish an accurate & efficient model for crop classification, including crop yield estimation based on soil, weather, & crop disease, crop classification based on growing phase, & so forth. accuracy about various machine learning (ML) methods used towards estimate crop yields is thoroughly examined in aforementioned study.